A new cestode parasite from the genus cotugnia from Ahmednagar district M.S. India. - Shukla, S J; Bhavare, V V; Borde, S N; Mohekar, A D (International Multidisciplinary Research Journal, 2012)
The genus Cotugnia was erected by Diamare (1893) [1] with type species C. diagonopora, collected from domestic fowl.Â  Eight specimens of the parasites were collected from the intestine of Gallus gallus domesticus. The present cestode have scolex quadrangular, absence of rostellar hooks, testes 63 in number, ovary oval, ootype small, rounded and postovarian. It was compared and differs from various five species and was considered as new species Cotugnia mohekarii.Â 